Linear static stress analysis of an automobile fuel tank - Muhamad Hazrul Hakimin, Abu Shaari (2009)
This thesis deals with linear static stress analysis of an automobile fuel tank. The objectives of this project are to develop a 3D model of an automobile fuel tank, finite element model, and linear static stress analysis of an automobile fuel tank. The thesis describes the finite element analysis techniques starting from the selection of best mesh types and size until the identification of the critical locations of an automobile fuel tank under static loading from. The material chosen for the automobile fuel tank was AISI S21900 Stainless Steel. The structural three-dimensional solid modelling of an automobile fuel tank was developed using the computer-aided drawing software. The strategy of the mesh optimization for the best mesh selection of finite element model was developed. The finite element analysis was then performed using MSC.NASTRAN code. The finite element model of the automobile fuel tank structure was analyzed using the linear elastic approach. The comparison of mesh configuration between tetrahedral with 4 nodes and tetrahedral with 10 nodes were made in many aspect of the results obtain including number of total nodes, displacements and stresses. From the results, it is observed that tetrahedral with 10 nodes give higher accuracy in many aspects than of tetrahedral with 4 nodes. The results obtain were then used to compare between three type of stress namely maximum principal stress, Von Mises stress and Tresca stress. The obtained results indicate that the stress not exceeding the tensile strength of the steel but rapid deformation will result leakage to the automobile fuel tank structure. The durability assessment results are significant to improve the automobile fuel tank venting system in the future. The results can also significantly help in the process of reducing the cost, and improve product reliability and customer confidence decesively.